PEMETAAN PINTU AIR DI DESA RASAU JAYA SATU KECAMATAN RASAU JAYA - Panjaitan, Monika Stella Leonita; Mulki, Gusti Zulkifli; Nurhidayati, ely (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2023)
The village of Rasau Jaya Satu is oneloflthl villagel inlthelDistrict of Rasau Jayalwhere the developmentlof an irrigation network was carried out to support the food self-sufficiency program in the 1970s. The development of irrigation networks is carried out by building irrigation canals and irrigation arrangements in the form of water gates on tertiary canals. This research was conducted by mapping the floodgates in the village of Rasau Jaya Satu. Thel first step is to lobtain lthe coordinates ofl the sluice using a map-based mobile application, namely Avenza. The process of taking the coordinates of the sluice points through direct field observations and documenting pictures of the sluice. The purposel of lthisl researchl is tol map lthe ldistribution lof floodgates usingl a software application and it is hoped that this can become a geographic system-based information medium in viewing the availability of floodgates. The result is that the mapping of sluice gates from the analysis mapped 45 sluice gates in the tertiary canal spread over 3 roads namely Secondary C Street, Pahlawan Street and Jalan Tepian Kapuas.